THE PROTAGONIST’S PERSONALITY IN PIDI BAIQ’S NOVEL DILAN DIA ADALAH DILANKU - Nurhayuni Harahap; Effendi Barus; Sri Wulan (JOURNAL OF LANGUAGE, 2022)
Literary psychology gives an important role to the analysis of psychological development of characterization in literary works.  In literary psychology, conflict is an upheaval among the id, ego, and superego. This study aims to describe the protagonist’s personality, focused on id, ego, and superego in the novel of Dilan Dia Adalah Dilanku Tahun 1990 by  Pidi  Baiq's. Personality is the characteristic patterns of thoughts, feelings, and behaviors that make a person unique. It is believed that personality arises from within the individual and remains fairly consistent throughout life. In Freud's psychoanalytic theory, the id is the primitive and instinctual part of the mind that contains sexual and aggressive drives and hidden memories, the super-ego operates as a moral conscience, and the ego is the realistic part that mediates between the desires of the id and the super-ego. The research is done by descriptive qualitative method by collecting and selecting the data from the novel. The additional sources of data are taken from respective references. The results show that the three parts of personality: id, ego, and superego are found in the personality of the protagonist and the elements of the psychic or personality are dominated by id and ego.